2011
DOI: 10.1016/j.maturitas.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Preventing cold-related morbidity and mortality in a changing climate

Abstract: Winter weather patterns are anticipated to become more variable with increasing average global temperatures. Research shows that excess morbidity and mortality occurs during cold weather periods. We critically reviewed evidence relating temperature variability, health outcomes, and adaptation strategies to cold weather. Health outcomes included cardiovascular-, respiratory-, cerebrovascular-, and all-cause morbidity and mortality. Individual and contextual risk factors were assessed to highlight associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 51 publications
4
87
0
Order By: Relevance
“…Multi-city studies reported the cold effects were most significant in warm regions (Langford and Bentham 1995;Wang et al 2012) or areas with moderate winter climates (Conlon et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Multi-city studies reported the cold effects were most significant in warm regions (Langford and Bentham 1995;Wang et al 2012) or areas with moderate winter climates (Conlon et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Fourth, caution should be exercised in interpreting these results because the study included only prefectures in Japan. Populations residing in different geographic regions may also be exposed to various extreme temperatures, and their adaptation may depend on individual-or neighborhood-level protection factors (Conlon et al 2011) as well as on cultural variables (Hancock et al 2008). Furthermore, exposure measurements were based on a capital city of a prefecture or the closest city if data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…These time series can be analyzed to yield information on how environmental conditions may contribute to increases in deaths and illness on a short-term time scale (days to weeks after the environmental exposure). In the last decade, numerous multicity time series analyses have demonstrated that cold and hot temperatures, as well as extremes of cold and hot temperature, are associated with increased death rates in the days after these weather conditions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These findings have important implications for understanding the health effects of climate change, given that climate change is increasing both the variability of temperatures and the frequency, duration, and intensity of heat waves (11)(12)(13).…”
mentioning
confidence: 99%